Normal - Borges, Afonso (2015)
In 2006, Naoto Fukasawaand Jasper Morrison creates the Super Normal exhibition, in which ordinary objects are exposed questioning the increasingly elitist role of design and suggesting an alternative vision. The choice of objects not only expressed their individual views, but also the approach of all the authors exposed, serving as a basis for the expansion of the concept of Super Normalfor a concept of normality. More comprehensive, built based on the concepts of each author mentioned, the idea of normalisolates the reactions to special, systematizes them on criteria of time and space, and seeks to absorb the work of many other authors and critics who discuss the product of similar points of view.